Ms. Marvel - Ahmed, Saladin (Marvel Worldwide, Inc., 2024)
"Ms. Marvel is back, and she's magnificent! But there's no such thing as business as usual in Jersey City. Aliens are wreaking havoc in Kamala's corner of the world, and they seem weirdly interested in Ms. Marvel and her family! Even if Kamala saves her hometown, will her life ever be the same? And what's all this business about a "Chosen One"? Kamala gets a new look, but literal corporate zombies derail her road trip with Zoe and Nakia! And when disaster strikes Kamala's family, she and Bruno are drawn closer together than ever before. But will Kamala's duties as Ms. Marvel come between them? Meanwhile, a new hero muscles in on Jersey City. Is the town big enough for Ms. Marvel and Amulet? And what happens when teen heroes are completely outlawed - in Kamala's name?!"--Provided by publisher